Bicuculline Reduces Neuroinflammation in Hippocampus and Improves Spatial Learning and Anxiety in Hyperammonemic Rats. Role of Glutamate Receptors - Malaguarnera, Michele; Llansola, Marta; Balzano, Tiziano; Gómez-Giménez, Belén; Antúnez-Muñoz, Carles; Martínez-Alarcón, Núria; Mahdinia, Rahebeh; Felipo, Vicente (Frontiers in Pharmacology, 2019)
Patients with liver cirrhosis may develop minimal hepatic encephalopathy (MHE) with mild cognitive impairment. Hyperammonemia is a main contributor to cognitive impairment in MHE, which is mediated by neuroinflammation. GABAergic neurotransmission is altered in hyperammonemic rats. We hypothesized that, in hyperammonemic rats: a) enhanced GABAergic tone would contribute to induce neuroinflammation, which would be improved by reducing GABAergic tone by chronic bicuculline treatment; b) this would improve spatial learning and memory impairment; c) modulation of glutamatergic neurotransmission would mediate this cognitive improvement. The aim of this work was to assess the above hypotheses. Bicuculline was administrated intraperitoneally once a day for 4 weeks to control and hyperammonemic rats. The effects of bicuculline on microglia and astrocytes activation, IL-1β content, on membrane expression of AMPA and NMDA glutamate receptors subunits in hippocampus and on spatial learning and memory and anxiety were assessed. Treatment with bicuculline reduces astrocyte activation and IL-1 but not microglia activation in hippocampus of hyperammonemic rats. Bicuculline reverses the changes in membrane expression of AMPA receptor subunits GluA1 and GluA2 and of NR2B (but not NR1 and NR2A) subunit of NMDA receptors. Bicuculline improves spatial learning and working memory and decreases anxiety in hyperammonemic rats. In hyperammonemia, enhanced activation of GABAA receptors in hippocampus contributes to some but not all aspects of neuroinflammation, to altered glutamatergic neurotransmission and to impairment of spatial learning and memory and anxiety, which are reversed by reducing activation of GABAA receptors with bicuculline